2004
DOI: 10.1007/s10562-004-6442-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Palladium on Iron Fischer?Tropsch Synthesis Catalysts

Abstract: Studies were conducted to investigate the effect of Pd on the Fischer-Tropsch Synthesis (FTS) selectivity, activity and kinetics as well as on the water-gas shift activity of an iron catalyst. Two palladium promoted catalysts (Pd0.002/Fe100 and Pd0.005/ Fe100) were prepared from a base Fe100/Si5.1 (atomic ratio) catalyst. Results of FTS over the two palladium promoted catalysts were compared to those obtained from the K/Fe/Si base catalyst and a Cu/K/Fe/Si catalyst. The results indicate that Pd enhanced the FT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 31 publications
0
16
0
1
Order By: Relevance
“…Richter and Baerns [11] examined Rh or Pd promoted Fe-Mn catalysts, and found that Rh and Pd increased FTS activity, decreased the olefin fraction and led to low molecular weight hydrocarbons. Davis [12] obtained the similar results on Pd promoted FeSiO 2 catalysts. Recent work down by Xu and Bartholomew [20] indicated that as Rh and Pd, Pt promoted FTS activity of a SiO 2 -supported iron catalyst, however, it suppresses methane selectivity and enhances C 2 + hydrocarbons selectivity.…”
Section: Introductionmentioning
confidence: 55%
See 1 more Smart Citation
“…Richter and Baerns [11] examined Rh or Pd promoted Fe-Mn catalysts, and found that Rh and Pd increased FTS activity, decreased the olefin fraction and led to low molecular weight hydrocarbons. Davis [12] obtained the similar results on Pd promoted FeSiO 2 catalysts. Recent work down by Xu and Bartholomew [20] indicated that as Rh and Pd, Pt promoted FTS activity of a SiO 2 -supported iron catalyst, however, it suppresses methane selectivity and enhances C 2 + hydrocarbons selectivity.…”
Section: Introductionmentioning
confidence: 55%
“…The effects of them on catalytic behavior of ironbased catalysts have been widely studied [7][8][9]. Some other active metals such as group VIII noble metals as promoters for FTS are seldom investigated in iron-based FischerTropsch catalyst system [10][11][12], despite that these metals (Ru, Pd, Re, Pt) are commonly used as promoters for cobalt-based FTS catalysts and have been carefully studied for years. As stated in several literatures, these noble metal promoters facilitate the reduction of cobalt-based FTS catalysts at much lower temperatures, presumably by spillover hydrogen from their surface to cobalt oxide [13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Iron-based catalysts typically contain copper [112][113][114][115][116][117][118] as a reduction promoter, although ruthenium [84], silver [113,119], palladium [120], and platinum [121] have been used as well. The addition of these metals to the catalyst formulation reduces the reduction temperature, which may result in a higher catalytic activity (see also Fig.…”
Section: Iron-based Catalystsmentioning
confidence: 99%
“…The price of the metals and the required relative amount of the reduction promoter should be kept in mind to judge the efficiency of these materials. For example, palladium [120] was shown to be effective at levels 100 fold less than copper, but the price of palladium is more than 1000 times the price of copper.…”
Section: Iron-based Catalystsmentioning
confidence: 99%
“…Many studies have described the phenomenological effects of promoters on FTS [4][5][6], without specific or rigorous attention to the effects of addition sequence. Therefore, we discuss here the differences in FTS performance between Fe-Zn-K 6 -Cu(Ru) 3 and Fe-ZnCu(Ru) 3 -K 6 from the point view of promoter addition sequence.…”
Section: Effect Of Promoters On Fischer-tropsch Synthesis Rate and Sementioning
confidence: 99%